Load-Bearing Capacity and Damages Morphology of Joints of AAC Masonry Walls Subjected to Shearing with Bending - GALMAN Iwona; BAJZECEROVÁ Viktória; KUŠNÍR Štefan; JASIŃSKI Radosław (Architecture, Civil Engineering, Environment, 2025)
The article presents the results of original research on wall connections made of autoclaved aerated concrete subjected to shear with bending. The shape of the test element and the test stand layout were innovatively selected based on the author’s research, a literature review, and numerical analyses. The study examined crack morphology and failure mechanisms, comparing load-displacement relationships for different types of connections. The obtained results were referenced against those from a reference model featuring a traditional masonry bond. In other test models, the connection was formed using steel connectors. For wall connections without a masonry bond, commonly available steel connectors from the construction market and a proprietary metal plate were used. The study demonstrated varied cracking and failure mechanisms, as well as significant differences in the behavior and load-bearing capacity of each connection type. The obtained results encourage further analyses to refine connections and explore new construction methods for wall joints.